Mercury and Cadmium contamination in ethnic groups from the Colombian Amazon: A panoramic overview of exposure sources and the general health status of the population. (2020)
Environmental exposure to heavy metals such as mercury (Hg) and cadmium (Cd) is currently a worldwide public health problem, especially in biodiversity hotspots such as the Amazon River basin, which houses large aquatic complexes, including the Amazon and Putumayo Rivers. These water bodies and their main tributaries are extensively degraded and threatened by dams, mining, and deforestation. In these areas, artisanal and small-scale gold mining activities are key contributors to Hg pollution in ecological media, as this element is employed for the separation of gold particles through an amalgamation process. In addition, human populations are highly exposed to other heavy metals, most significantly Cd, as it is likely mobilized during mining activities. In addition to mining, the Colombian Amazon faces a significant disappearance of forest mass as a result of the conversion of land into agricultural plantations or grazing areas, logging, and road construction, which is carried out illegally or, at least, irregularly in many cases. This situation co-exists with other issues that are due to poverty, and which, in turn, lead to micronutrient deficiencies, including Se. Unfortunately, this panorama represents a risk to the health of indigenous communities that not only base their diet and economy on the cultivation of autochthonous species, but also on the consumption of fresh and canned fish as main sources of protein. Given the risks that heavy metals represent to human health, biological indicators are essential tools in the assessment of health issues generated by exposure to them. These indicators, when associated with the socio-demographic characteristics of the population, the frequency of fish consumption, the diet, and the specific symptomatology related to heavy metal exposure; provide valuable information that can be used to estimate risks to the health of vulnerable communities. Although multiple studies have shown levels of Hg and Cd contamination in the Amazon region, few have focused on the relationship between these concentrations, the load of the essential element Se, and their effects on exposed individuals (i.e. changes in the hematological parameters of populations). In order to understand the current state of Hg contamination in the Colombian Amazon, the first study in this thesis documented concentrations of this element in nine indigenous communities of the Tarapaca Village (on the Cotuhe and Putumayo rivers), an area inhabited by groups that have a traditional lifestyle that is highly affected by the mining activities carried out there. Subsequently, hair and fish samples were taken from residents of the Municipality of Puerto Nariño, which is located at the southern extreme of the Colombian Amazon, in order to evaluate the interactions between Hg, Cd and Se, and possible risks and associated with changes in the hematological levels of the population. Likewise, the isotopic composition of Hg of the inhabitants of this municipality was evaluated in order to confirm that their exposure to this element occurred through the consumption of fish, thus highlighting the influence of gold mining in this area. Finally, additional results are presented related to the presence of As and Pb, as well as eight essential elements in brands of canned tuna and sardines consumed by the inhabitants of this region. In order to meet these objectives, a total of 190 hair samples were taken from indigenous people living at the Tarapaca village. The overall mean T-Hg level of these samples was 10.6±0.4 μg/g, with values ranging from 0.61 to 31.1 μg/g. Based on recommendations from the United States Environmental Protection Agency (USEPA), 99.5% of the samples exceeded the maximum level of 1.0 μg/g Hg. This Hg content was significantly associated with fish consumption (ρ=0.253; p<0.001), and, according to a health survey that was simultaneously conducted, at least 24.7% of the volunteers manifested some signs and symptoms related to Hg poisoning. Thus, this study demonstrates the extensive Hg contamination currently found in the Colombian Amazon environment, a situation that could impact the quality of life of its vulnerable indigenous groups. In the context of the second project that was carried out, Hg, Cd, and Se concentrations in fish, as well as the magnitude of exposure and hematological conditions of adult citizens from Puerto Nariño (Colombian Amazon) were assessed. Among fish samples, greater Hg concentrations were found in higher trophic level species, including Rhaphiodon vulpinus (880±130 ng/g) and Pseudoplatystoma tigrinum (920±87 ng/g). These species presented both the highest hazard quotients and the lowest Se:Hg molar ratios found in the study; conditions that may represent significant health risks. Several samples of Mylossoma duriventre and Prochilodus magdalenae had Cd levels greater than the recommended limits. Mercury concentrations in human hair and blood were 5.31 µg/g and 13.7 µg/L, respectively. All hair samples exceeded the 1.0 μg/g threshold set by the USEPA, whereas 93% of the volunteers had Hg levels in blood above 5 μg/L, suggesting that there is elevated exposure in the Amazon environment. In relation to Cd, the mean value found in the blood of the volunteers was 3.1 µg/L, with 21% of samples surpassing 5 µg/L. Additionally, eighty-four percent of participants presented Se deficiencies (<100 μg/L). There was also a significant association between fish consumption and T-Hg in hair (ρ=0.323; p=0.032) and blood (ρ=0.381; p=0.011). In this last matrix, Se correlated with Cd content, whereas lymphocytes were inversely linked to Hg concentrations. The results of this study showed that there was extensive exposure to Hg through fish consumption in this population, which may be linked to negative impacts on hematology parameters within the community. Given that hair reflects the body's load of Hg, in the third project, Hg stable isotopes in hair were used as tracers of potential sources of this element, taking the indigenous communities from Pueblo Bello (Sierra Nevada de Santa Marta) as comparison populations. The slope obtained for hair samples from Pueblo Bello (1.197±0.050, 2SE, n=36) and the Δ199Hg and Δ201Hg anomalies indicated that the Hg levels within the population are mostly the result of a photochemical Hg demethylation process derived from a magnetic isotope effect. Thus, the Mass Independent Fractionation signature found in the hair of volunteers was acquired before the methylmercury was incorporated into the food web. A significant trend was found between δ202Hg and Δ199Hg in the individuals from Pueblo Bello. Given that the obtained Δ199Hg/δ202Hg slope (0.917±0.222; 2SE, n=36) was very low compared to theoretical photodemethylation trends (a slope of 2.43±0.10, 1 SE), it was concluded that the observed tendency is most likely produced by binary mixing, and is not related solely to a photochemical process. Despite the fact that fish is not their only protein source, the highest Δ199Hg values corresponded to people who consumed mainly canned fish (especially sardines and tuna) and fresh marine fish species. According to δ202Hg (range: +1.08 to +2.46‰) and Δ199Hg (range: -0.01 to +0.57 ‰) signatures of the hair samples from Puerto Nariño (Amazon), it was possible to determine that this population is remarkably homogeneous, with similar sources of Hg exposure. Since hair Δ199Hg values of the Amazon inhabitants are close to 0, these were much lower than those of the Sierra Nevada de Santa Marta inhabitants, but similar to the signature of Hg ores, which highlights the influence of the gold mining activities carried out in the region. Finally, in the fourth project, the concentrations of eight essential elements [Chromium (Cr), Manganese (Mn), Iron (Fe), Cobalt (Co), Nickel (Ni), Copper (Cu), Zinc (Zn), and Se] and four elements of toxicological concern [Arsenic (As), Cd, Hg, and Lead (Pb)] were determined in selected brands of canned sardines and tuna marketed in Latin America and commercially available in the Amazon, with the aim of estimating risk-based fish consumption limits. The Hg content found during this study was much higher than that observed in previous surveys carried out by our research group. According to the Hazard Quotients obtained, all brands may present some risk in terms of this element; especially brand F, in which levels up to 3.1 µg/g were measured. Similarly, sardine samples surpassed the reference limits of Mn and As. According to the observed trend, we highly encourage the use of stricter quality control measures in retail chains by industries, in order to guarantee safe levels of these elements in fishery products.